Flunitrazepam, a 7-nitro-1,4-benzodiazepine that is unable to bind to the indole-benzodiazepine site of human serum albumin - Chuang, Victor; Otagiri, M. (Elsevier, 2001)
Benzodiazepine (BDZ) is generally thought to bind to site II of human serum albumin (HSA), also known as the indole-BDZ site, which is located at subdomain III A of the molecule. However, differences in the binding characteristics of BDZ drugs with HSA have been reported. The photolabeling profiles of HSA with [(3)H]flunitrazepam (FNZP) in the presence and absence of diazepam (DZP) were shown to be identical, suggesting that each drug primarily binds to different regions. The results of fluorescent probe displacement experiments showed that FNZP failed to decrease the fluorescence of dansylsarcosine to an extent similar to that of DZP.In the photoinhibition experiment, site I and site II ligands failed to inhibit the photoincorporation of [(3)H]FNZP to HSA. In order to evaluate the photolabeling specificity of FNZP, an attempt was made to photolabel alpha(1)-acid glycoprotein (AGP) which also binds BDZ with similar affinity as HSA. The effect of myristate (MYR) and DZP on the FNZP photolabeling of these two major drug binding plasma proteins was examined. Photoincorporation was inhibited when HSA was photolabeled with [(3)H]FNZP in the presence of MYR but not in the presence of DZP. Conversely, DZP inhibited the photolabeling of [(3)H]FNZP to AGP. These results suggest that FNZP interacts with HSA at regions which are not located in the preformed binding pocket of subdomain III A.